An overview of recent applications of reduced graphene oxide as a basis of electroanalytical sensing platforms. (March 2018) - Rowley-Neale, Samuel J.; Randviir, Edward P.; Abo Dena, Ahmed S.; Banks, Craig E.
Graphical abstract: This article overviews the use of reduced graphene oxide as the basis of electrochemical sensors from the last 2 years; guidelines for the progression of this field are also given. Highlights: Graphene research is a highly active and productive field offering potential applications. Reduced graphene oxide (rGO) is more often the material of choice for electrochemical sensors and associated applications. rGO based electrochemical sensors from the past two years are overviewed. Guidelines for the progression of this field are also given. Abstract: The academic literature using graphene within the field of electrochemistry is substantial. Graphene can be fabricated via a plethora of routes with each having its own unique merits (e.g. cost, fabrication time, quality and scale) and reduced graphene oxide (rGO) is more often the material of choice for electrochemical sensors and associated applications due to its ease of fabrication and ability to be mass produced on the kilogram scale. This review overviews pertinent developments in the use of rGO as the basis of electroanalytical sensors (2016–2017); guidelines for the progression of this field are also given.